2010
DOI: 10.1177/1524839909353023
|View full text |Cite
|
Sign up to set email alerts
|

Appraising Quantitative Research in Health Education: Guidelines for Public Health Educators

Abstract: Many practicing health educators do not feel they possess the skills necessary to critically appraise quantitative research. This publication is designed to help provide practicing health educators with basic tools helpful to facilitate a better understanding of quantitative research. This article describes the major components—title, introduction, methods, analyses, results and discussion sections—of quantitative research. Readers will be introduced to information on the various types of study designs and sev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 5 publications
0
26
0
Order By: Relevance
“…Specific criteria were used to critically appraise each paper . Seven criteria were evaluated: (a) study design, (b) sample representativeness, (c) control group, (d) validity of measurement, (e) droupout/missing data, (f) blindness, and (g) credibility assessment . No controlled trials or randomized controlled trials (RCT) studies were found therefore the criterion 6 about blindness was superfluous and omitted.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Specific criteria were used to critically appraise each paper . Seven criteria were evaluated: (a) study design, (b) sample representativeness, (c) control group, (d) validity of measurement, (e) droupout/missing data, (f) blindness, and (g) credibility assessment . No controlled trials or randomized controlled trials (RCT) studies were found therefore the criterion 6 about blindness was superfluous and omitted.…”
Section: Methodsmentioning
confidence: 99%
“…The study was conducted according to the recommendation for systematic reviews 22,23 and quality assessment for the type of studies included in the review. [24][25][26][27][28][29] Each study was examined independently, and standardized criteria were used to critically appraise the different types of studies. 26,27 In the assessment of the included articles, only the QoL part of each study has been focused.…”
Section: Methodsmentioning
confidence: 99%
“…Jack et al (2010) suggest that any quantitative research publication typically include the following key components: publication title, abstract, introduction, method, data analysis, results and discussion/conclusion. These components are consistent with those found in qualitative research publications.…”
Section: The Key Components Of a Qualitative Research Publicationmentioning
confidence: 99%
“…Jack et al (2010) offer general guidance and recommendations for increasing one’s skills and confidence in reading scientific publications that included…”
mentioning
confidence: 99%
“…[10] Eight articles were identified to be reviewed. These nine articles referred only to occupational therapy and physiotherapy programmes.…”
Section: Methodsmentioning
confidence: 99%